All inkjet-printed flexible wireless power transfer module: PI/Ag hybrid spiral coil built into 3D NiZn-ferrite trench structure with a resonance capacitor. (August 2019) - Bissannagari, Murali; Kim, Tae-Hyung; Yook, Jong-Gwan; Kim, Jihoon
Abstract: The conceptual evolution of rigid-to-flexible in future electronic platforms requires unprecedented innovations in materials and manufacturing technologies to suit the new usage environment of flexible electronics. This research presents a novel method to implement a flexible wireless power transfer (WPT) module with a low coil resistive loss by overcoming the technical limitations associated with the rigidity of ceramic materials and the thickness resolution of inkjet printing. To ensure the low resistive loss of the WPT module, a high-aspect-ratio form of the coil consisting of alternating layers of polyimide (PI) and Ag is built into the 3D NiZn-ferrite (NZF) spiral trench structure. A resonance capacitor is also inkjet-printed and integrated with the WPT coil to minimize the final dimension of the WPT module. The hybrid (PI/Ag) coil in the 3D NZF spiral trench with the resonance capacitor is then inserted into polydimethylsiloxane (PDMS) to render the entire 3D inkjet-printed structure flexible. The performance of the flexible WPT module is verified by charging a mobile phone under a flexible environment. The flexible WPT module is also successfully built into a wristband to demonstrate wireless charging of a smart watch. Graphical abstract: Image 1 Highlights: A flexible WPT module was prepared by embedding fully inkjet-printed PI/Ag hybrid coils in 3D trench structures into PDMS. This work presents a unique way to ensure the flexibility of WPT modules comprising less-flexible metals and ceramic materials. The performance of the flexible WPT module was demonstrated by transmitting wireless power to a mobile phone and a smart watch.